Walisongo's Role In Actulating The Islamic Religion And Javanese Culture - Firman, Syaiful Firmanzah; Arizqi Ihsan Pratama (Cita konsultindo, 2022)
The entry of Islam into the archipelago has occurred since the XII century. The spread of Islamic religious teachings did not escape the role of the wali songo, especially on the island of Java. Long before Islam entered the natives, the Javanese people had long embraced the teachings of animism, dynamism, Hinduism and Buddhism. acculturation in the context of Islamic religion and culture is the interaction between Islamic teachings and local culture. However, it should be underlined that local culture is still strong, so that there is a blend of local culture and Islamic culture. This combination is known as cultural acculturation. This study uses a qualitative research method type of literature study. Using various kinds of literature sources such as books, journals, and magazines as data collection. The result of the research is that the process of Islamization in the land of Java runs peacefully without any major conflicts. That illustrates that Islam is the religion of Lil Rahmatil